Optimizing the Utility of Allium cepa L. var. aggregatum (sibuyas Tagalog) for the Allium Test by Elucidating its Mitotic Periodicity and Rhythmicity Under Varying Light Conditions - Matias, Ambrocio Melvin A.; Fontanilla, Ian Kendrich C. (Science Diliman: A Journal of Pure and Applied Sciences, 2011)
The occurrence of pattern of mitotic activity has long been studied in different plants; in the onion Allium cepa, determination of its mitotic activity has led to its utilization in the Allium test for cytotoxicity and mutagenicity of test substances. In this study, the pattern of mitotic activity of A. cepa var. aggregatum and the effect of light exposure on mitotic activity were determined to test the utility of A. cepa L. var. aggregatum as an alternative to the common onion, A. cepa, for the Allium test. Bulblets of A. cepa var. aggregatum were allowed to root for three days in tap water under three different set-ups: constant light exposure set-up (Light), constant dark set-up (Dark) and 12 hours light-12 hours dark set-up (Light-Dark). The root tips from the bulblets were then excised and subjected to microscopic observation for the mitotic index (MI) every hour after the third day. The results showed no significant difference observed across the three set-ups. However, MI for the Dark and Light set-ups were periodic, showing peaks or maxima of MI falling between 11 AM and 12 PM, whereas that of Light-Dark set-up was rhythmic, having an hourly fluctuation, but also showed maximum between 11 AM and 12 PM. It is recommended that A. cepa var. aggregatum root tips be excised between 11 AM and 12 PM for the Allium test. Keywords: Allium cepa var. aggregatum, periodicity, rhythmicity, mitotic index, light, Allium test